1984
DOI: 10.1016/0014-5793(84)81393-9
|View full text |Cite
|
Sign up to set email alerts
|

Water‐soluble 17 and 23 kDa polypeptides restore oxygen evolution activity by creating a high‐affinity binding site for Ca2+ on the oxidizing side of Photosystem II

Abstract: Exposure of detergent-isolated preparations of the Photosystem II complex to 2 M NaCl releases watersoluble 17 and 23 kDa polypeptides; the inhibited rate of oxygen evolution activity is stimulated by addition of Ca2+ ) FEBS Lett. 167, 127-1301. Reactivation of oxygen evolution activity by Ca2+ requires the presence of the ion in high (mM) non-physiological concentrations. Using a new dialysisreconstitution procedure we have shown that rebinding of the 17 and 23 kDa polypeptides restores oxygen evolution activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
135
2

Year Published

1985
1985
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(146 citation statements)
references
References 12 publications
(12 reference statements)
9
135
2
Order By: Relevance
“…Salt-washing or reconstituting salt-washed particles did not alter the amount of Ca'+ required, although it did change the magnitude of the response ( fig.3A). Ca2+ produced the largest increase in activity with salt-washed spinach PS II particles and mangrove oxygen-evolving particles, both of which are devoid of the 23-and l&kDa polypeptides ( fig.4, [9,16] [19] reported that the 23-and 18-kDa proteins volved in oxygen evolution (lane 5). Western blotreduced the Ca2+ requirement; however, they did ting confirmed that the salt-washed spinach parnot control Cl-in their assays, and it has been ticles and the mangrove membranes had lost the shown that the 23-kDa protein increases the affini-23-and 18-kDa proteins (not shown, but see [la]).…”
Section: Fig3 Ca2+ Requirement For Oxygen Evolution In Spinach Ps Imentioning
confidence: 97%
“…Salt-washing or reconstituting salt-washed particles did not alter the amount of Ca'+ required, although it did change the magnitude of the response ( fig.3A). Ca2+ produced the largest increase in activity with salt-washed spinach PS II particles and mangrove oxygen-evolving particles, both of which are devoid of the 23-and l&kDa polypeptides ( fig.4, [9,16] [19] reported that the 23-and 18-kDa proteins volved in oxygen evolution (lane 5). Western blotreduced the Ca2+ requirement; however, they did ting confirmed that the salt-washed spinach parnot control Cl-in their assays, and it has been ticles and the mangrove membranes had lost the shown that the 23-kDa protein increases the affini-23-and 18-kDa proteins (not shown, but see [la]).…”
Section: Fig3 Ca2+ Requirement For Oxygen Evolution In Spinach Ps Imentioning
confidence: 97%
“…For these samples, reconstitution of activity required long term incubation in the presence of Ca 2+ prior to activity assays. The presence of the PsbP subunit presumably blocks rapid access of Ca 2+ to its binding site in the OEC (Ghanotakis et al 1984b;Miyao and Murata 1986;Ono and Inoue 1988), and this in turn makes it difficult to assess the actual Ca 2+ affinity of the site in this preparation. Recent experiments probing acid-treated PSII with reductants showed that access to the Mn cluster by NH 2 OH was increased relative to that of a larger reductant (hydroquinone), and that Ca 2+ reconstitution closed this pathway (Vander Meulen et al 2002;.…”
Section: Introductionmentioning
confidence: 99%
“…Parallel research has been directed towards identifying which poly- 90% (4-7, 15, 16, 21, 25, 27) when determined in the presence of saturating concentrations of Cl-. Subsequently, it was shown (6,7,15,16) that addition of 10 to 20 mM Ca2+ to 17,24 kDless, Cl-sufficient spinach PSII membranes increased rates of 02 evolution as much as 4-to 6-fold to rates sometimes nearly equivalent to those observed with unextracted membranes. However, no Ca2' additions were necessary to observe substantial period-4 oscillations of the S-states with only about 25% disconnection of the S-state complexes from PSII traps (12).…”
Section: Introductionmentioning
confidence: 99%